Factores socioeconómicos y su incidencia en la deserción académica de los estudiantes no locales de la carrera de Sociología del año 2023. - Shacay Cuenca Jazmin Yamanua (2025)
The present research work is carried out at the State University of Bolívar and is aimed at students of the Sociology major, since its purpose is to investigate the main socioeconomic factors that influence academic dropout during the period March-September 2023. within which a specific focus is made towards non-local students. Likewise, there are theoretical lines that have an interdisciplinary model that encompasses the reproductionist that is applied within the sociology of education from the perspective of Campdepadrós and Pulido; critical education and pedagogy from Paulo Freire and conflict theory from Becker were the most present. Furthermore, it is shown that the students of the Sociology major, who mostly belong to cities other than Guaranda, are the ones who have processed the most negative experiences in their being, such as: costs of living, accommodation, transportation and nutrition, low level of adaptation to the environment as it generates academic dropout. A quantitative methodology is used through surveys and the results obtained are generalizable, which allows researchers and university authorities to develop policies and programs based on concrete evidence. Keywords:Academic dropout, socioeconomic, reproductionist model, human capital, education.